Branding and Product Packaging Mentoring for SMEs (UMKM) to Increase Product Selling Value - Budi Margono; Hilmi Wiranawata (PT. Anagata Sembagi Education, 2026)
Small and medium enterprises (UMKM/SMEs) in Indonesia face persistent challenges in marketing and product competitiveness, largely due to the absence of consistent branding and professional packaging. This community service study aimed to assess the impact of structured branding and packaging mentoring on the selling value of UMKM products in Yogyakarta, Indonesia. Using a participatory action research (PAR) approach, the program engaged 25 UMKM participants across five activity stages: branding workshop, logo design assistance, packaging design training, market simulation trial, and monitoring and evaluation. Quantitative pre-post assessments and qualitative interviews were employed to measure outcomes. Results demonstrated a significant increase in brand awareness (from 23% to 71%), average selling price (from IDR 8,500 to IDR 14,200 per unit), and packaging compliance with BPOM labeling standards (from 12% to 88%). Monthly revenue among participants rose by an average of 81%. The findings confirm that integrated branding and packaging mentoring constitutes an effective intervention to enhance the economic competitiveness of Indonesian SMEs, with implications for community development programs and public policy supporting UMKM sustainability